Influence Of 200 mm Hg Occlusion Pressure on Arterial Blood Flow in Skeletal Muscles and Physical Working Capacity - Kęstutis Bunevičius; Albinas Grūnovas; Karolis Tijūnaitis (Lithuanian Sports University, 2018)
Research background and hypothesis. Different weights, resistance, scope of work, rest periods, frequency, and performance velocity are used to increase strength in training sessions. The traditional training facility with high resistance can be replaced by low resistance while limiting muscle blood flow. Hypothesis: a single 15-minute 200 mm Hg occlusion pressure can affect physical working capacity and blood flow intensity. Research  aim.  was  to  analyze  changes  in  the  intensity  of  the  calf  muscle  arterial  blood  flow  and  physical working capacity with and without 200 mm Hg pressure occlusion.    Research  methods.  were  dynamometry,  ergometry,  venous  occlusive  plethysmography.  The  control  group included six and experimental group - 12 male athletes in endurance sports. In both groups we recorded arterial blood flow at rest and after 75% of maximum voluntary contraction force (MVC) physical work lifting a weight until complete fatigue. Between the first and second physical workloads in the experimental group we applied 15 min occlusion with 40 mm wide cuff in the groin area. Research results. During the physical load in the control group, arterial blood flow significantly increased, and during recovery it did not reach to baseline. In the experimental group arterial blood flow significantly increased and during recovery it did not reach the baseline. Blood flow intensity both the first and the second physical loads altered analogically. Before the second physical load in the experimental group, 200 mm Hg occlusion had a negative effect on skeletal muscle working capacity compared with the passive rest in the control group. Discussion and conclusions. Occlusion of 200 mm Hg in the groin area reduces arterial blood flow intensity in calf skeletal muscles. Immediately after the removal of 200 mm Hg occlusion, arterial blood flow intensity increases and then decreases to its original value. 200 mm Hg occlusion pressure reduces blood flow intensity in the skeletal muscles.    Before  the  second  physical  load,  200  mm  Hg  occlusion  decreases  skeletal  muscle  working  capacity compared with passive rest in the control group. Keywords: occlusion, physical working capacity, arterial blood ﬂow.